Angiography Analysis of Variations of the Posterior Segment of the Circle of Willis - Alma Voljevica; Amela Kulenović; Eldan Kapur; Ilvana Vučković (Biomolecules & Biomedicine, 2005)
Cerebral-vascular diseases present one of the leading problems of the modern mankind. They are followed by the risk of high mortality rate, and as such cause high level of disability with people who survive cerebral-vascular incident (stroke, apoplexy). Researches done so far proved that beginning, course and result of the cerebral-vascular diseases depend immensely of the possibility to establish collateral blood circulation and first of all on so called tertian level that is actually the circle of Willis. The circle of Willis, thanks to communicating segments, provide detour way to procure parts of the brain which, due to insufficiency, do not get enough quantity of blood. In this particular study by the analysis of 150 MRI patient’s angiographies of the circle of Willis that had been processed at the Radiology Institute of the Clinic Center of University in Sarajevo, we tried to present the most common variations of the posterior segment of the circle of Willis with patients who did not have signs of the cerebral-vascular diseases. The analysis included two target groups (above 60 years old and younger than 34 years old) and both genders. By the analysis of the angiographies of the circle of Willis we reached following results: complete posterior configuration of the circle of Willis has been found with all patients in 54% of cases, but in some slightly higher percentage complete posterior configuration is noted with younger category of patients compared to elderly patients, and in some higher percentage with female compared to male patients. Out of variations that damage the posterior segment of the circle of Willis the first one, according to the frequency of occurring, is the variation of the type of unilateral fetal sort of posterior cerebral artery, and then the variation marked as unilateral aplasia or hypoplasia of the posterior communicating artery.